Unmet Psychosocial Needs and Quality of Life of Young Women with Breast Cancer: A Scoping Systematic Review - SHAZA, HASAN; Keng Sheng, Chew (Asia Pacific Organization for Cancer Prevention (APOCP), 2024)
Background: The diagnosis and treatment of breast cancer are very distressing for young women and can result in a lot of unmet psychosocial needs and a lower quality of life. Objective: Although unmet psychosocial needs in young women with breast cancer can negatively impact their quality of life, these needs have not been systematically reviewed. The primary objective of this scoping review was to identify the categories of unmet psychosocial needs among young women with breast cancer. The secondary objective was to examine the relationship between these unmet psychosocial needs and their quality of life. Methods: Five electronic databases (MEDLINE from the National Library of Medicine, Cumulative Index of Nursing and Allied Health Literature (CINAHL), SCOPUS, Web of Science WOS, and Google Scholar), as well as reference lists of relevant literature were systematically searched to identify the relevant literature following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement for reporting systematic reviews. Results: From an initial yield of 2505 articles, 30 articles were included and analyzed. The results identified 13 main domains of unmet psychosocial needs among young women with breast cancer: information needs, psychological needs, physical/symptoms needs, fear of recurrence and spreading, identity-related needs, social needs, sexual needs, social support, financial support, practical needs, spiritual needs, communication-related issues with health care providers, and coping needs. Data were extracted and summarized in a narrative synthesis. Conclusion: Ongoing assessment of informational needs and a clear understanding of the relationship between unmet psychosocial needs and quality of life are essential for healthcare providers to develop robust support systems for young women with breast cancer.